Feasibility of intravenous injection of pig plasma extracellular particles into rats: an acute study - Nicolás Cherñavsky; Stepheny C. de Campos Zani; Marcelo A. Mori; Nina Torres Zanvettor (European Journal of Biological Research)
Extracellular particles (EPs), especially small extracellular vesicles (EVs), extracted from young animals are increasingly being studied in animal models as agents for regeneration and rejuvenation, with studies using EPs from one species injected into another showing no immune reaction. In this study, we aimed to investigate if the injection of Pig Plasma Extracellular Particles (PPEPs) into rats would produce an acute immune or toxic reaction. Blood from a young pig was collected, PPEPs were isolated by size exclusion chromatography and injected into young male Sprague-Dawley rats, while the control group received a sterile saline injection. After 9 days, the animals were euthanized and their organs were histologically analyzed for signs of cellular damage or immune infiltration. The treated rats showed no signs of acute immunological reaction, behaving normally immediately after the injections and during the 9 days since the first injection. Throughout the trial period, the animals continued gaining weight normally and the histological analysis of their liver, kidney and spleen showed no signs of acute toxicity. PPEPs from young animals do not cause an acute immune or toxic response when injected intravenously into young male Sprague-Dawley rats.